Tinjauan Normatif Terhadap Perjanjian Pranikah Bagi Pasangan Lintas Negara - Najah, Ratu Sakinatun; Sofiani, Nurul Aini; Anugrah, Jorian; Prayoga, Satria (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
A prenuptial agreement is a legal instrument that outlines the agreement between a prospective husband and wife before entering into marriage. In Indonesia, the legal basis for prenuptial agreements is regulated by Law Number 1 of 1974 concerning Marriage and Article 29, which was later expanded by Constitutional Court Decision Number 69/PUU-XIII/2015. In the context of cross-border couples (marriages between Indonesian citizens and foreign nationals), prenuptial agreements have a special dimension that concerns not only property but also citizenship status, land rights, and implications for different legal regimes. This article examines prenuptial agreements for cross-border couples through a philosophy of science approach, examining ontology, epistemology, and axiology. Normative analysis is used to understand the position of prenuptial agreements in positive law, while also assessing the urgency, rationality, and social benefits of such agreements.